2013
DOI: 10.4314/ajtcam.v10i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chinese medical herbs-Huiru Yizeng Yihao on hyperprolactinemia and hyperplasia of mammary gland in mice

Abstract: The study investigated the pharmacodynamism and mechanism of Chinese medicinal formula-Huiru Yizeng Yihao (NO.1 HRYZ) on the model rats of hyperpro-lactinemia and the model rats of hyperplasia of mammary gland (HMG), and studied the internal connection between hyperprolactinemia and HMG.. The hyperprolactinemia rat models were established by injecting metoclopramide dihydrochloride in the back of rats. The model rat of HMG was prepared by injecting estradiol in the thigh muscle of the rats and progesterone con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Previous studies report higher E2 and PRL concentrations in MGH model induced with estradiol benzoate and progesterone, whereas PR concentrations were lower compared with those in the control group (Wang et al, 2013a). However, lower E2 and P concentrations are observed, whereas higher PRL concentrations are observed in HPRL model induced with metoclopramide dihydrochloride compared to the concentrations in the control group (Wang et al, 2013b). These findings imply that the three hormones play important roles in regulation of MGH and lactation.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies report higher E2 and PRL concentrations in MGH model induced with estradiol benzoate and progesterone, whereas PR concentrations were lower compared with those in the control group (Wang et al, 2013a). However, lower E2 and P concentrations are observed, whereas higher PRL concentrations are observed in HPRL model induced with metoclopramide dihydrochloride compared to the concentrations in the control group (Wang et al, 2013b). These findings imply that the three hormones play important roles in regulation of MGH and lactation.…”
Section: Discussionmentioning
confidence: 72%
“…When extraneous stimulations act on human body, some sex hormones secrete abnormally leading to many kinds of disease such as HMG, hyperprolactinemia, hysteromyoma and infertility. The sex hormone disorder occurs in HMG rat models [18].…”
Section: Discussionmentioning
confidence: 99%
“…When extraneous factors act on the human body, sex hormone secretion becomes abnormal leading to the occurrence of a variety of diseases such as hyperprolactinemia, HMG, hysteromyoma, and infertility. In mammals, PRL can regulate mammary glandogenesis, promote milk secretion, and trigger and maintain lactation through autologous and paracrine as a cytokine [15,16]. Our previous research revealed that PRL played a very important role in the formation of HMG [9].…”
Section: Discussionmentioning
confidence: 99%
“…Needless to say, a low expression of CRYAB enhances mitochondrial dysfunction including mitochondrial depolarization, the enhancement of mitochondrial Evidence-Based Complementary and Alternative Medicine permeability, and release of cytochrome c [13,14]. However, when CRYAB inhibits caspase activation to be resistant to apoptosis and promotes oncogenic transformation in the selection of cells, HMG forms and even leads to the onset of mammary tumors [15]. In our study, antiapoptotic protein CRYAB and protein Bcl-2 were increased, while promoting apoptosis protein caspases-3, caspases-8, caspases-9, and Bax, tumor suppressor protein p53, and cytochrome c were decreased.…”
Section: Discussionmentioning
confidence: 99%